2016
DOI: 10.1001/jamapsychiatry.2016.0934
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes in Women With Untreated Antenatal Depression Compared With Women Without Depression

Abstract: Our results contrast with what is, to our knowledge, the only previous systematic review that examined the question of untreated depression because we found significant risks of 2 key perinatal outcomes, preterm birth and low birth weight. These are important results for pregnant women and clinicians to take into account in the decision-making process around depression treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
231
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(252 citation statements)
references
References 45 publications
9
231
2
10
Order By: Relevance
“…The presence of these symptoms at high levels can lead to unfavorable maternal and perinatal outcomes. (2)(3)(4)(5) The least frequent was the thought about injuring oneself. However, its presence at all stages shows the importance of a specific screening tool to identify pregnant women at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of these symptoms at high levels can lead to unfavorable maternal and perinatal outcomes. (2)(3)(4)(5) The least frequent was the thought about injuring oneself. However, its presence at all stages shows the importance of a specific screening tool to identify pregnant women at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Depression may persist in the postpartum period and compromise parental behavior, the relationship with the partner and family, the process of mother-child bonding, and the child's cognitive, motor and psychosocial development. (2)(3)(4)(5) Studies on depression and its effects in the prenatal period are recent, dating back two decades, with an increase thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…However, another meta-analysis reported that perinatal depression was associated with a lower gestational age, but not a lower birth weight [39]. One limitation of these two meta-analyses is that they included studies potentially confounded by SSRI medication use, as in these primary studies women taking anti-depressants were not excluded; thus, a more recent meta analysis was conducted to compare neonatal outcomes in pregnant women with depression who did not receive treatment (i.e., pharmacological or nonpharmacological) and women without depression [40]. Results showed that pregnant women with depression who did not receive treatment were at increased risk for lower birth weight compared to women without depression, with a trend toward higher risks with more severe depression.…”
Section: Perinatal Ssris Birth Weight and Maternal Depressionmentioning
confidence: 99%
“…In addition to animal models, a number of human studies have linked maternal distress with adverse birth outcomes, including a greater risk of preterm birth, increased birth-related complications and lower birth weight, as well as longer-term health effects on the offspring [19][20][21]. Maternal distress during pregnancy may also cause long-term effects on the cognitive development of the infant, as well as leading to an increased risk of behavioral problems.…”
Section: Effects Of Maternal Prenatal Stress On the Offspringmentioning
confidence: 99%